MANAJEMEN KEUANGAN DALAM KESEJAHTERAAN KELUARGA PETANI DI DESA SIDODADI KECAMATAN TEMPUREJO KABUPATEN JEMBER - Rizki, Miftahur; Supeni, Retno Endah; Izzuddien, Ahmad (Growth, 2023)
This research focuses on examining how farmers manage and manage finances in the family. The purpose of this study was to find out about how farmers manage finances and see how it affects family welfare. In this study using a qualitative approach and descriptive research type. According to the BKKBN, welfare itself is divided into 5 namely pre-prosperous, prosperous type I, prosperous type II, prosperous type III and prosperous type III+. The results of this study indicate that of the 30 farmers studied there were 11 farmers who were in type I welfare, 3 farmers were in type II welfare, and 16 farmers were in type III welfare. However, these results are different if according to theory (Sukmawati et al.,2020) which measures welfare from income, if according to this research then out of the 30 farmers studied there were 10 farmers who were not financially prosperous, 12 farmers who were almost financially prosperous and 8 farmers who were financially prosperous.